Star wars. the empire strikes back - Lucas, George; Kurtz, Gary (Star Wars trilogy., 2000)
Luke Skywalker seeks out the mysterious jedi master Yoda while Han Solo and Princess Leia outrun the Imperial fleet en route to Cloud City.